2021
DOI: 10.1084/jem.20210236
|View full text |Cite
|
Sign up to set email alerts
|

Broad and potent neutralizing human antibodies to tick-borne flaviviruses protect mice from disease

Abstract: Tick-borne encephalitis virus (TBEV) is an emerging human pathogen that causes potentially fatal disease with no specific treatment. Mouse monoclonal antibodies are protective against TBEV, but little is known about the human antibody response to infection. Here, we report on the human neutralizing antibody response to TBEV in a cohort of infected and vaccinated individuals. Expanded clones of memory B cells expressed closely related anti-envelope domain III (EDIII) antibodies in both groups of volunteers. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 94 publications
3
50
0
Order By: Relevance
“…A subset of cross-reacting monoclonal antibodies protected against POWV, Langat virus (LGTV), and TBEV infection in a mouse model. In another study, broadly neutralizing antibodies against tick-borne flavivirus were discovered in humans after TBEV infection [34]. The antibodies were able to bind the TBEV EDIII domain and exert broad neutralization activity against multiple tick-borne flaviviruses, including…”
Section: Discussionmentioning
confidence: 99%
“…A subset of cross-reacting monoclonal antibodies protected against POWV, Langat virus (LGTV), and TBEV infection in a mouse model. In another study, broadly neutralizing antibodies against tick-borne flavivirus were discovered in humans after TBEV infection [34]. The antibodies were able to bind the TBEV EDIII domain and exert broad neutralization activity against multiple tick-borne flaviviruses, including…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the lateral ridge of the D3 domain of glycoprotein E is the main receptor binding site on the surface of the TBEV virion (reviewed in Mandl CW, 2005 and Kellman EM et al, 2018). This supported by the fact that the majority of highly neutralizing and protective mice-derived monoclonal antibodies and some human-derived antibodies against flaviviruses are directed to this region of the D3 domain (Roehrig JT, 2003; Oliphant T et al, 2005; Sánchez MD et al, 2005; Dai L et al, 2016; Agudelo M et al, 2021). Since the ch14D5 antibody recognizes the epitope located on the lateral ridge of the D3 domain, we assume that one of the major mechanisms of the antiviral action of this antibody is blocking the binding of the virion to cellular receptors.…”
Section: Discussionmentioning
confidence: 99%
“…At the moment, experimental structures are only available for three antibodies against TBEV: 19/1786 (Fuzik T et al, 2018), Mab 4.2 (Yang X et al, 2019) and T025 (Agudelo M et al, 2021). Comparison of the structure determined in this study with these structures showed that the epitope of the ch14D5 antibody is adjacent and partially overlap with other epitopes, but it is not identical to them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations